AB1058 Renal Impairment among Postmenopausal Women with Osteoporosis from A Large Health Plan in Israel. (10th June 2014) - Yu, J.; Goldshtein, I.; Ish-Shalom, S.; Sharon, O.; Modi, A.
Abstract : Objectives: To estimate the proportion of patients with renal impairment among postmenopausal osteoporotic women within a large health plan in Israel. Methods: This was a retrospective analysis of Maccabbi electronic medical records (EMR) in Israel. Women aged ≥55 years, with a recorded osteoporosis diagnosis or osteoporosis-related fracture (date for 1st such diagnosis was defined as index date) between 1/1/2007 and 12/31/2012, who were enrolled in health plan for ≥1 year prior to and after index were included. Patients' minimum serum creatinine level (Scr) during one year pre-index to one year post-index was utilized to calculate glomerular filtration rate (eGFR), using Modification of Diet in Renal Disease (MDRD) equation. Stage 1-5 of renal impairment was classified using the MDRD renal impairment staging system by eGFR: normal ≥90; mild 60 – 89; moderate 30– 59; severe 15 – 29, and failure<15 mL/min/1.73 m 2 respectively. Results: 18, 101 patients were included in the analysis. The mean age (± standard deviation [SD]) of these patients was 66.7±9.0 years, and 35.5% of patients had a fracture at index. Patients with renal function of stage 1-5 accounted for 21.7%, 47.3%, 14.3%, 15.9%, 1.0%, and 0.1% respectively of all patients. 2.3% of those patients had eGFR levels <35 mL/min/1.73 m 2 ; the rate was 1.5% for patients with osteoporosis diagnosis and 3.9% for patients with fractures; the rate was higher among older patients aged ≥70 (4.3%) than younger patients (0.5%). Conclusions: This analysis showed that 2.3% of osteoporotic women had renal impairment (eGFR levels <35 mL/min/1.73 m 2 ) to a level at which the commonly used bisphosphonates such as alendronate, risedronate and ibandronate are not recommended. This limitation indicates a need for therapeutic alternatives that have been demonstrated to reduce fracture risk in osteoporotic patients with severe renal insufficiency. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2053